Organ-specific safety profile of bioinspired short antimicrobial peptides in zebrafish embryos - Da’as, Sahar Isa; Afreen, Hajira; Fathima, Aseela; Hani, Ahmad M.; Mohamed, Nura A.; Rahman, Md Mizanur; Burgon, Patrick G.; Crovella, Sergio; Abou-Saleh, Haissam (Frontiers in Pharmacology, 2025)
ObjectiveAntimicrobial peptides (AMPs) are key components of the innate immune system, exhibiting broad-spectrum antibacterial and immunomodulatory activities. Building on these properties, we designed bio-inspired short antimicrobial peptides (BSAMPs) using computational and bioinformatics approaches. Following promising in vitro results demonstrating selective anticancer activity against colorectal cancer cells, this study aimed to investigate the in vivo organ-specific safety and toxicity profiles of two selected BSAMPs—Peptide C (GVLCCGYRCCSKWGWCGTT) and Peptide E (CWWMTRRAWR)—using the zebrafish model.MethodZebrafish embryos were exposed to various concentrations of Peptide C and Peptide E. Phenotypic toxicity endpoints—including Lethal Concentration 50 (LC50), cardiotoxicity, neurotoxicity, and hepatotoxicity—were assessed.ResultThe LC50 values for Peptide C and Peptide E were determined to be 162.2 μg/mL and 131.82 μg/mL, respectively. Peptide C caused minimal cardiovascular effects below 150 μg/mL but induced neurotoxic and hepatotoxic effects at concentrations exceeding 100 μg/mL. Peptide E exhibited developmental toxicity at concentrations above 100 μg/mL, along with cardiotoxic effects such as reduced heart rate, variable locomotion patterns, and clear hepatotoxic responses.ConclusionThis study highlights distinct organ-specific toxicity profiles for Peptides C and E and underscores the importance of careful preclinical evaluation of BSAMPs. The zebrafish model provided valuable insights into the potential safety concerns of these peptides, supporting their further investigation and refinement for future therapeutic development.